Stimulating a Gradual and Progressive Shift to Personalize Learning for All: There is Magic in the Middle - Dr. Autumn R Turk (Middle Grades Review, 2021)
This essay contends that personalized professional learning can support the shift towards a culture of personalized learning at the middle school level, with the potential to make a district-wide impact. If you have ever worked in a middle school, you would agree there is a sense magic and contagious energy within middle school students. Middle school is often an overlooked and untapped resource when considering efforts to transform school and district culture. Middle school students start to develop passions and a voice for advocacy, making agency a powerful accelerator when students channel their collective energy towards a shared vision for change. This past year has placed tremendous pressures on our educators, school leaders, students, and parents; yet, it has also offered us a remarkable opportunity to re-imagine our educational system by focusing on a more personalized approach to learning for both our students and adults. Educators have re-entered the learner’s seat with an immediate urgency to enhance their instructional practices so they may engage students in learning and manage their classrooms in new and nontraditional learning environments. The result of this shift has yielded many benefits, such as the use of technology for learning and curation of digital curriculum resources; however, it has also created a renewed need to focus on the efficacy and professional learning of educators. Rising concerns with equity, learning loss, and mental health have added additional pressure for school leaders, teachers, and support staff. Therefore, there is a need to reimagine our vision for the future of education and strategically plan flexible pathways to make our vision a reality. A vision for embedding ongoing personalized coaching within professional learning communities can improve teacher efficacy, enhance collaborative data analysis and lesson planning, and transform school culture to maximize personalized learning for all students.
Keywords: teacher efficacy; personalized professional learning; evocative coaching; personalized learning; school culture; middle school; social-emotional learning